Emerging Epigenetic Therapeutic Targets in Acute Myeloid Leukemia - Wingelhofer, Bettina; Somervaille, Tim C. P. (Frontiers in Oncology, 2019)
Acute myeloid leukemia (AML) is a genetically heterogeneous malignancy for which treatment options have been largely limited to cytotoxic chemotherapy for the past four decades. Next-generation sequencing and other approaches have identified a spectrum of genomic and epigenomic alterations that contribute to AML initiation and maintenance. The key role of epigenetic modifiers and the reversibility of epigenetic changes have paved the way for evaluation of a new set of drug targets, and facilitated the design of novel candidate treatment strategies. More recently, seven new targeted therapies have been FDA-approved demonstrating successful implementation of the past decades’ research. In this review, we will summarize the most recent advances in targeted therapeutics designed for a focused group of key epigenetic regulators in AML, outline their mechanism of action and their current status in clinical development. Furthermore, we will discuss promising new approaches for epigenetic targeted treatment in AML which are currently being tested in pre-clinical trials.